Phenotypes of masked hypertension: isolated ambulatory, isolated home and dual masked hypertension - Stergiou, GS; Kyriakoulis, KG; McManus, RJ; Andreadis, EA; Jula, A; Kollias, A; Lindroos, A; Ntineri, A; Schwartz, C; Niiranen, TJ (Lippincott, Williams and Wilkins, 2019)
Objectives: Masked hypertension (MH) is defined as normal office blood pressure (OBP) and elevated ambulatory (ABP) or home blood pressure (HBP). This study assessed MH identified by each of these two methods. Methods: A retrospective analysis of cross-sectional data in treated and untreated adults from Greece, Finland and UK who had OBP, HBP and 24-h ABP measurements was performed. Dual MH was defined as normal OBP and elevated HBP and ABP, isolated ambulatory MH as normal OBP and HBP and elevated ABP and isolated home MH as normal OBP and ABP and elevated HBP. Results: Of 1971 participants analyzed, 445 (23%) had MH on ABP and/or HBP (age 57.1 ± 10.8 years, men 55%, treated 49%). Among participants with any MH, 215 had dual MH (48%), 132 isolated ambulatory MH (30%) and 98 isolated home MH (22%). Moreover, 55% had high-normal, 35% normal and 10% optimal OBP. In logistic regression analysis isolated ambulatory MH was predicted by younger age (OR 0.35, P < 0.01 per 10 years increase), whereas isolated home MH was predicted by older age (OR 2.05, P < 0.01 per 10 years increase). Conclusion: Masked hypertension diagnosed by ABP and not HBP monitoring or the reverse is not uncommon. Age appears to be the most important determinant of isolated ambulatory or home MH, with the former being more common in younger participants and the latter in older ones. Only half of participants with MH have high-normal OBP, whereas the rest have lower levels.